DETERMINAN RETURN SAHAM: KAJIAN TENTANG PERAN ANALISIS FUNDAMENTAL - Nurlaili, Ismi; Prasojo (Faculty of Economics and Business University of Mataram, 2024)
In making investment decisions, investors need to conduct fundamental analysis to understand the company's intrinsic value and make more precise and informed decisions. Previous research on fundamental analysis has not yet provided consistent results in explaining the determinants of stock returns. This research aims to analyze and deliver the latest empirical evidence about the influence of fundamental analysis as measured by DPR, DPS, EPS, FCF, PCFR, EVA, REVA, and MVA on stock returns. Quantitative testing was conducted using panel data regression analysis on 48 companies listed in the Indonesian Sharia Stock Index (ISSI) during 2018-2022. The research results show that fundamental analysis, measured by DPR, DPS, EPS, EVA, and REVA, positively and significantly influences stock returns. In contrast, FCF, PCFR, and MVA do not affect stock returns. These results provide theoretical contributions relevant to signaling theory and agency theory.